Primary structures and partial toxicological characterization of two phospholipases A2 from Micrurus mipartitus and Micrurus dumerilii coral snake venoms - Rey Suárez, Paola (2017)
Snake venom phospholipases A2 (PLA2) share high sequence identities and a conserved structural scaffold, but show important functional differences. Only a few PLA2s have been purified and characterized from coral snake (Micrurus spp.) venoms, and their role in envenomation remains largely unknown. In this report, we describe the isolation, sequencing and partial functional characterization of two Micrurus PLA2s: MmipPLA2 from Micrurus mipartitus and MdumPLA2 from Micrurus dumerilii, two species of clinical importance in Colombia. MmipPLA2 consisted of 119 amino acid residues with a predicted pI of 8.4, whereas MdumPLA2 consisted of 117 residues with a pI of 5.6. Both PLA2s showed the conserved 'group I' cysteine pattern and were enzymatically active, although MdumPLA2 had higher activity. The two enzymes differed notably in their toxicity, with MmipPLA2 being highly lethal to mice and mildly myotoxic, whereas MdumPLA2 was not lethal (up to 3 μg/g body weight) but strongly myotoxic. MdumPLA2 displayed higher anticoagulant activity than MmipPLA2 in vitro and caused more sustained edema in the mouse footpad assay. Neither of these enzymes was cytolytic to cultured skeletal muscle C2C12 myotubes. Based on their structural differences, the two enzymes were placed in separate lineages in a partial phylogeny of Micrurus venom PLA2s and this classification agreed with their divergent biological activities. Overall, these findings highlight the structural and functional diversity of Micrurus venom PLA2s.